Computational and Physical Examination About the Aspects of Fluid Flow Between Two Coaxially Rotated Disks by Capitalizing Non-fourier Heat Flux Theory: Finite Difference Approach - Bilal, Sardar; Tassaddiq, Asifa; Majeed, A. H.; Nisar, Kottakkaran Sooppy; Ali, Farhad; Malik, M. Y. (Frontiers in Physics, 2020)
This pagination is executed to exemplify flow features exhibited by viscous fluid between two coaxially rotated disks. Thermal analysis is performed by using Cattaneo-Christov heat flux theory. Porosity aspects are also taken in to account. Mathematically structured non-linear PDEs are transmuted into non-linear ODEs by employing Karman transformations. Afterwards, solution is heeded by applying implicit finite difference scheme renowned as Keller box method. Interpretation of flow controlling parameters on axial, tangential and radial components of velocity, thermal distribution is exhibited. Assurance of computed data is done by managing comparison for skin friction coefficients at walls of disks. From the attained outcomes it is addressed that the magnitude of axial and radial velocities diminishes at lower disk contrary to upper disk for intensifying magnitude of Reynold number. Increment in tangential component of velocity is also demonstrated for uplifts values of Reynold number. It is also concluded that thermal field decrements for increasing of Pr and thermal relaxation parameter. It is worthy to mention that shear drag coefficient at wall of lower disk decreases conversely to the wall shear coefficient magnitude at wall of upper disk.